How to Unprime or Halt Automatic Good-bad Evaluation of Others’ Behaviors - TONG, Yuk-Yue (Institutional Knowledge at Singapore Management University, 2012)
Only entity theorists of personality believing in fixed traits (but not incremental theorists believing in malleable traits) form automatic good-bad evaluation of others’ behaviors. Automatically formed evaluations can be “unprimed” by expression (Sparrow & Wegner, 2006). Automatic evaluative process can be halted by removal of an evaluative goal.